2012
DOI: 10.3390/su4081787
|View full text |Cite
|
Sign up to set email alerts
|

The Race for Evolutionary Success

Abstract: Abstract:The Earth appears to be at the beginning of sixth massive species extinction. This paper balances a review of the forces threatening species survival with a comprehensive scan of factors that could act as counterweights. These factors could lead to four types of evolution-cultural, regulatory, ecological, and technological-that could individually or in combination avert massive species extinction if humans implement solutions faster than new problems arise. Implications and future research opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Individuals are often faced with making daily decisions in a setting and context they did not create, in terms of who has political power, who has control over resources, and, in a broader sense, what infrastructural and technological options are available and why. What is well noted is the imperative of social and cultural systems to change, to adapt, and evolve to meet the sustainability challenges at all levels [53]. Thus, interrogating the SLR literature (including GL content) from a socio-technical consideration views the data from an institutional and governance context and asks the question of who is really responsible for the development and practice of sustainable behaviour in our society and how this can be progressed.…”
Section: Socio-technical Approach-systems Of Provisionmentioning
confidence: 99%
“…Individuals are often faced with making daily decisions in a setting and context they did not create, in terms of who has political power, who has control over resources, and, in a broader sense, what infrastructural and technological options are available and why. What is well noted is the imperative of social and cultural systems to change, to adapt, and evolve to meet the sustainability challenges at all levels [53]. Thus, interrogating the SLR literature (including GL content) from a socio-technical consideration views the data from an institutional and governance context and asks the question of who is really responsible for the development and practice of sustainable behaviour in our society and how this can be progressed.…”
Section: Socio-technical Approach-systems Of Provisionmentioning
confidence: 99%
“…Using the framework presented in Fig. 3, Tonn and Stiefel (57) conducted an environmental scan focusing on nonhuman species extinction and found that the aggregated influences appear to be lessening threats to nonhuman species over the next several decades.…”
Section: Environmental Scanning Approachmentioning
confidence: 99%
“…The challenge of transitioning towards resilient socio-ecological systems is compounded by complex system interactions [33] and the overall effects of adaptation strategies "must be considered strategically and holistically" [34]. For example, in the case of climate change several authors have highlighted complexity as a defining feature (see for example [14,35]).…”
Section: Complexity and Interdependencymentioning
confidence: 99%